An Atypical Case of Myxedema Coma with Concomitant Nonconvulsive Seizure - Pratik Patel; Mikhael Bekkerman; Cristina Varallo-Rodriguez; Rajendra Rampersaud (Case Reports in Critical Care)
Hypothyroidism is a prevalent condition in the general population that is treatable with appropriately dosed thyroid hormone replacement medication. Infrequently, patients will present with myxedema coma, characterized by hypothermia, hypotension, bradycardia, and altered mental status in the setting of severe hypothyroidism. Myxedema coma has also been known to manifest in a number of unusual and dangerous forms. Here, we present the case of a woman we diagnosed with an uncharacteristic expression of myxedema coma and nonconvulsive seizure complicated by a right middle cerebral artery infarct.